Affirmation of the Rights and Obligations of Couriers in Cash on Delivery Marketplace Transactions - Wahono Wahono; Tri Susilowati; Naya Amin Zain (Dinasti Research, 2024)
The rapid development of e-commerce in Indonesia has given rise to various innovations in payment systems, including the Cash on Delivery (COD) method, which provides advantages for consumers to pay for goods in cash upon receipt. While this system offers convenience for consumers, it presents significant challenges for couriers as intermediaries in such transactions. Couriers often face financial and psychological risks due to payment rejections by buyers. In such situations, couriers' positions become vulnerable due to often inadequate legal protections and company policies that do not always favor couriers' interests. This writing aims to examine the rights and obligations of couriers in COD transactions through legal and social approaches, as well as to explore the challenges they encounter in carrying out their duties. This writing identifies weaknesses in regulations and offers recommendations to strengthen the protection of couriers' rights in Indonesia. It is hoped that this research can serve as a basis for regulatory improvements so that the rights and obligations of couriers in COD transactions can be more clearly and fairly affirmed, thus supporting the creation of a more balanced and sustainable e-commerce ecosystem.